The sins of the father - Archer, Jeffrey, 1940- (New York : St. Martin's Press, 2012)
A second installment in a planned five-part series finds Harry despairing of a marriage to Emma and joining the Merchant Navy before assuming the identity of a fallen American soldier whose past proves even more turbulent than Harry's own
Keywords: Families -- England -- History -- 20th century -- Fiction; World War, 1939-1945 -- Fiction; Family secrets -- Fiction; British -- United States -- History -- 20th century -- Fiction; Domestic fiction; Voyages and travels -- Fiction; Marital conflict -- Fiction; Impostors and imposture -- Fiction; Deception -- Fiction